1995
DOI: 10.1172/jci118241
|View full text |Cite
|
Sign up to set email alerts
|

Comparative distribution of the alpha 1(IV), alpha 5(IV), and alpha 6(IV) collagen chains in normal human adult and fetal tissues and in kidneys from X-linked Alport syndrome patients.

Abstract: We have shown previously that the 5' ends of the genes for the ca5(IV) and ca6(IV) collagen chains lie head-to-head on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
4
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 43 publications
2
70
4
1
Order By: Relevance
“…a6(IV) chain was seen in the distal tubular segment and BCBM. This is in good agreement with the earlier results on both rat and human kidney (Miner and Sanes, 1994;Ninomiya et al, 1995;Peissel et al, 1995;Yoshioka et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…a6(IV) chain was seen in the distal tubular segment and BCBM. This is in good agreement with the earlier results on both rat and human kidney (Miner and Sanes, 1994;Ninomiya et al, 1995;Peissel et al, 1995;Yoshioka et al, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Rabbit antisera raised against collagen a3(IV), a4(IV) and a5(IV) were characterized by Miner and Sanes (1994) and that raised against collagen a6(IV) by Peissel et al (1995). MAb M3F7 to a1, a2(IV) was described earlier (Foellmer et al, 1983) and was purchased from Developmental Studies Hybridoma Bank (University of Iowa, IA).…”
Section: Antibodies and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In the human and rodent kidney, immunohistochemical studies have shown a low-level expression of ␣1(IV) to ␣2(IV) in mature GBM whereas the ␣3(IV) to ␣5(IV) chains are highly expressed. [22][23][24][25][26][27] Little is known about the different isoforms of triple-helical type IV collagen molecules, 5,28 and their supramolecular organization in the different basement membranes. However, different subpopulations of NC1 hexamers, which reflect the association of two triple-helical molecules within the type IV collagen network, have been described recently in GBM as well as in other basement membranes.…”
mentioning
confidence: 99%
“…Type IV collagen is assembled from a family of distinct ␣-chains designated ␣1 to ␣6, which are encoded by six different genes, COL4A1 to COL4A6, respectively. 7 The glomerular basement membrane (GBM) is composed of the ␣1 to ␣5 chains, 8,9 which are assembled in triple helices that in turn selfassemble into supramolecular networks. Two distinct ␣1/ ␣2-containing and ␣3/␣4/␣5-containing networks have been identified at the biochemical level.…”
mentioning
confidence: 99%